Beyond Symbolism: Women's Challanges for Substantive Representation in Budget Politics - Ratnaningsih Damayanti; Restu Karlina Rahayu (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2025)
The presence of women in legislative institutions represents a form of symbolic representation obtained through general elections. Generally, there is an expectation from the public, particularly voters, that through the presence of women in legislative institutions, female legislators will focus more on issues that impact women. This research is an extension of previous studies on women in politics, where the focus has often been on the process of women entering political institutions. This study examines women's involvement in the budgeting process in Batu City, East Java. The research method used is qualitative research. Data was collected from document analysis, observation, and interviews with female DPRD (Regional Representative Council) members and local government bureaucrats. The findings show that the executive uses a technocratic approach to control the regional budgeting process. The budgetary board discusses the budget draft with the attending legislative members in the legislative branch. The budgeting procedure limits the participation of women legislative members in the budget committee. The participation of female DPRD members in budgeting is hindered by the dominance of political parties and the patriarchal culture within political parties. Not all female DPRD members on the budgetary board can be involved in the budgeting process; only senior politicians can join the budget committee. Thus, at the regional level, the representation of women in the DPRD is still in the category of symbolic representation.